FAKTOR – FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERAPAN SISTEM PERPAJAKAN - Kurnia Sari Dewi; Meiliyah Ariani; Yudhistira Adwimurti (Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of convenience, information technology, security and taxpayer satisfaction on the effectiveness of the implementation of the case study e-filling tax system in Sunter Agung Village, North Jakarta City. Sample selection was done by using the Accidental Sampling method. The data in this study were collected from taxpayers who pay taxes and are registered as taxpayers in Sunter Agung Village, North Jakarta. The number of samples used were 100 respondents. The sampling technique used is multiple regression in SPSS ver. 22. The results of this study partially prove the ease of e-filling taxation has a positive and significant effect, tax information technology has a positive and significant effect, while tax security has no positive and significant effect. Taxpayer satisfaction has a positive and significant effect on the effectiveness of the implementation of the e-filling tax system.